PEMERIKSAAN TERHADAP ANGGOTA DPRD PROVINSI YANG TERLIBAT KASUS TINDAK PIDANA TERKAIT DENGAN ASAS EQUALITY BEFORE THE LAW - Ade Hendrawan, I Made; Novy Purwanto, I Wayan (Kertha Wicara : Journal Ilmu Hukum, 2014)
This paper titled "CHECKING THE PROVINCE PARLIAMENT CRIME CASE INVOLVED ARE CONTRARY TO THE PRINCIPLES equality before the law". This paper is a normative legal research that use statutory approach, this paper aims to determine the legal proceedings against the Provincial Parliament allegedly committing a crime. In accordance with the principle of equality before the law which is also stipulated in Article 27 paragraph (1) of the 1945 Constitution, all citizens have equal status in the eyes of the law. However, if a crime allegedly committed by State officials in this paper, namely the Provincial Parliament for the legal process requires the written approval of the Minister of the Interior on behalf of the President. This is not in accordance with the principle of equality before the law.
Keywords: Crime, State Officials, Equality Before The Law